The Capacity Planning Problem Considering the Procurement of Bottleneck Machines and Auxiliary Tools - Chen, Yin-Yann; Fan, Hsiao-Yao; Shih, Chiung-Wen; Huang, Po-Han (Lecture notes in engineering and computer science, 2014)
This study explores issues on medium-term multi-plant capacity allocation and expansion planning in the TFT-LCD industry. Since the Array stage is the bottleneck of this production network, our research objective is to simultaneously seek an optimal capacity allocation plan and capacity expansion policy under single-stage, multi-generation and multi-site structures. Capacity allocation decides on profitable product mixes and allocated production quantities of each product group at each production site. An increment strategy for the numbers of bottleneck machines and auxiliary tools-"photo mask" is proposed to increase the flexibility of production. The decisions include how to allocate appropriately the forecast demands of products among multiple sites and how to decide on the numbers of bottleneck machines and auxiliary tools. A mathematical programming model of capacity planning is formulated to solve this problem and find the best solution, which considers practical characteristics and constraints of TFT-LCD manufacturing. Finally, an industrial case study modified from a Taiwanese TFT-LCD manufacturer is illustrated and sensitivity analysis of some influential parameters is also addressed.